2022
DOI: 10.1038/s41598-022-14744-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of religiosity and religious participation in the relationship between depressive symptoms and cognitive impairment among older Indian adults

Abstract: Due to different nature of social engagements of older adults in South Asian countries specially attributed to the traditional family-based care and support, beneficial effects of religiosity and religious involvement on mental health and cognitive function in older age might be different than those in the Western world. Yet, there is a paucity of research in these countries on the role of religion in moderating the relationship between late life depression and cognition. This study explored the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 83 publications
2
8
0
Order By: Relevance
“…In contrast, studies on cognitive abilities in developing countries find older women often perform worse than older men 87 88. Moreover, earlier studies in India reported a relatively lower cognitive functioning level among older women than men 46–48 89. In line with the previous literature, the current findings suggest a significant female disadvantage in cognitive function among older Indian adults and call for special attention with regard to public policy frameworks, clinical practice and future research.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, studies on cognitive abilities in developing countries find older women often perform worse than older men 87 88. Moreover, earlier studies in India reported a relatively lower cognitive functioning level among older women than men 46–48 89. In line with the previous literature, the current findings suggest a significant female disadvantage in cognitive function among older Indian adults and call for special attention with regard to public policy frameworks, clinical practice and future research.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have also documented a higher level of life satisfaction among religious people than non-religious individuals [ 56 ]. Thus, alternative social support mechanisms such as religious participation can be promoted in terms of enhancing mental wellbeing among older Indian adults [ 57 ]. Furthermore, the study has found that living arrangement satisfaction plays an important role in determining life satisfaction in older age.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the comfort and peace caused by spiritual beliefs and practices may reduce feelings of anxiety and depression, as well as improve mood, promote optimism and increase self-esteem. 41 Finally, greater importance of spirituality or religion in life may help to prevent depression by increasing cortical thickness or preventing cortical thinning. 42,43 This present study also found that age ≥65 years old, being female, hypertension and severe medical comorbidity were risk factors for the development of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Second, religious involvement as a form of social interaction may enhance social networks, and in this way have a positive impact on mental health. Third, the comfort and peace caused by spiritual beliefs and practices may reduce feelings of anxiety and depression, as well as improve mood, promote optimism and increase self‐esteem 41 . Finally, greater importance of spirituality or religion in life may help to prevent depression by increasing cortical thickness or preventing cortical thinning 42,43 …”
Section: Discussionmentioning
confidence: 99%